Miyazakiworld a life in art - Napier, Susan (Yale University Press, 2018)
The story of filmmaker Hayao Miyazaki's life and work, including his significant impact on Japan and the world—'an essential work in anime scholarship.” (Angelica Frey, Hyperallergic) A thirtieth†‘century toxic jungle, a bathhouse for tired gods, a red†‘haired fish girl, and a furry woodland spirit—what do these have in common?